Studio television production and directing : concepts, equipment, and procedures - Utterback, Andrew Hicks (New York, NY : Routledge, 2023)
"Master the fundamentals of studio production procedure and become an effective leader on set. Gain fluency in essential studio terms and technology and acquire the skills you need to make it in the industry. Elegant, accessible, and to the point, the new and updated third edition of Andrew H. Utterback's Studio Television Production and Directing is your back-to-the-basics guide to studio-based lighting, set design, camera operations, floor direction, technical direction, audio capture, graphics, prompting, and assistant directing. Whether you are an established studio professional or a student looking to enter the field, this book provides you with the technical expertise you need to successfully coordinate live or taped studio television in the digital age. The third edition of this book includes an expanded glossary and has been updated throughout, including new material on visualization walls and virtual sets, technical directing, camera mounts (including drones and robotic pedestals), narrative diagramming, updated newsroom computer systems, and more. An updated companion website includes visual representations of the topics discussed in the book"--
1. Overview of Equipment and Positions; -- 2. Audio; -- 3. Technical Directing -- 4. Lighting and Sets; -- 5. Studio Cameras and Floor Directing; -- 6. Newsroom Computer Systems, Prompter, Graphics, Playback, Remotes, Engineering; -- 7. Rundowns, Scripts, Video Clip Information; -- 8. Assistant Directing and Directing; -- Appendix; -- Activities; -- Glossary; -- Index.
Includes index.
Includes bibliographical references and index.
Andrew Hicks Utterback, Ph.D. is a Professor in the Department of Communication at Eastern Connecticut State University. As a former Senior Production Technician, he writes from professional experience that includes program credits in master control, as grip, gaffer, A1, camera operator, playback, floor director, technical director, assistant director, and director. As a Professor in the field for 24 years, Dr. Utterback presents the fundamentals of studio television production and directing in a simple and straightforward manner that is clear and unintimidating.
Keywords: Television -- Production and direction; Television broadcasting -- Technological innovations